Practice guideline: Statement regarding treatment for suspected slowly progressive type 1 diabetes (SPIDDM; probable) cases (English version) - Akira Shimada; Eiji Kawasaki; Norio Abiru; Takuya Awata; Yoichi Oikawa; Haruhiko Osawa; Hiroshi Kajio; Junji Kozawa; Kazuma Takahashi; Daisuke Chujo; Shinsuke Noso; Tomoyasu Fukui; et al. (Journal of Diabetes Investigation)
Abstract Insulin treatment should be introduced in patients with slowly progressive type 1 diabetes (SPIDDM; definite), according to the revised diagnostic criteria of SPIDDM (2023). In contrast, SPIDDM (probable) patients are in a non‐insulin‐dependent state; therefore, a more flexible treatment can be considered, although sulfonylurea agents should be avoided. Insulin treatment has been shown to maintain endogenous insulin secretion capacity in SPIDDM (probable); however, this does not mean that all SPIDDM (probable) patients should use insulin from the early phase. Dipeptidyl peptidase‐4 inhibitors and biguanides might be the treatment of choice for SPIDDM (probable), but no evidence exists for other hypoglycemic agents. In any case, careful monitoring of the endogenous insulin secretion capacity should be carried out, and if a decrease in insulin secretion capacity is suspected, a change in treatment should be considered to prevent progression to an insulin‐dependent state.